Pengaruh Penggunaan Akun Twitter @collegemenfess Terhadap Minat Mahasiswa Mengikuti Kegiatan Kampus Merdeka - Maharani, Wanda Erika; Purnawan, Ni Luh Ramaswati; Gelgel, Ni Made Ras Amanda (E-Jurnal Medium, 2023)
Along with the development of Twitter, there is an autobase that have a functions as an intermediary medium for Twitter users. @collegemenfess is the largest autobase account that share information based on the needs of students and disseminating about Kampus Merdeka activities. The purpose of this study is to describe whether there is an effect of using Twitter @collegemenfess on students' interest in participating in Kampus Merdeka activities. This study using uses and effect theories as well as explanative quantitative methods by survey and measuring up to 100 respondents. The data analysis used simple linear regression analysis with SPSS 26. The result of the study shows the impact of @collegemenfess' twitter account on the interest of university students following 58% of Kampus Merdeka activities. There is a positive and unionized influence on the use of twitter account @collegemenfess on the interest of students attending free Kampus Merdeka Keywords: Social Media, Twitter @collegemenfess, Kampus Merdeka, Interest